Meningkatkan Hasil Belajar PAK melalui Problem Based Learning (PBL) Tema Kemampuan dan Keterbatasanku bagi Peserta Didik Kelas VII Fase D SMP Negeri 1 Sawo - Nina R. Elfrida Elisa Parhusip; Timotius Tote Jelahu; Modestus Haryono; Marta Lea Resti Prana Widya (PROSIDING SEMINAR NASIONAL PENDIDIKAN DAN AGAMA, 2024)
This research aims to increase student interest and learning outcomes in Catholic Religious Education subjects through the application of the Problem Based Learning (PBL) learning model for class VII students at SMP Negeri 1 Sawo. This research uses the classroom action research (PTK) method which is carried out in two cycles. The first and second cycles discuss My Abilities and Limitations. The subjects in this research were Class VII-B students at SMP Negeri 1 Sawo for the 2024/2025 academic year, consisting of 12 people. The main techniques for collecting data are carried out by means of tests and observations, while supporting techniques use interviews and documentation. The research results show that the application of the PBL model can significantly increase student interest and learning outcomes. This is shown by increased student activity in learning, increased test scores, and positive student responses to learning.